Use of Non Toxic Materials for Whitefly Control and Growth Enhancement in Crisphead Lettuce - Molin, W. T. (College of Agriculture, University of Arizona (Tucson, AZ), 1995)
Field studies were conducted in Yuma and Tucson in 1993 to determine the effect of several non toxic substances purported to enhance growth and yield of lettuce, and to determine whether these treatments have an effect on whitefly populations. Five applications of the treatments were made beginning four weeks after planting and continuing at weekly intervals. Results indicated that there may be some positive effects of foliar applied methanol and nutrient (nitrogen/iron) treatments, as well as, from the use of Capture insecticide.